METODE FADHLI FAME LANER UNTUK ALAT 3D LASER SCANNER - Fadhli Umar Lubis (Journal of Mechanical Engineering and Mechatronics, 2018)
The 3D laser scanner that will be used in this study is a design tool for students of the 2007 Mechanical Engineering Department. This tool has been validated and used in several studies. Improvements to the 3D Laser Scanner tool are still being carried out, especially in the accuracy of the geometry of the 3D model produced and the time required in the processing of the scanning data. The research was conducted with the aim to increase the results obtained from the scanning process in order to have maximum results and have a fast processing time. In the research conducted, there are several differences with the previous method, namely the use of Visual Basic, supporting software, placing the camera and laser and camera settings. Based on the results of the study, the final results of the scan show the size of the test object has a smaller deviation of 8.12% for height, 0.8% for width and 19.3% for the neck, compared to previous studies of 61.09% for height, 51.8% for width and 40.75% for neck. For the time of the scanning process, there is a shortening of time that is very far compared to previous research, namely the time needed for 1 minute 56 seconds, while in the previous study it took 1 hour 41 minutes 37 seconds.